Selective recruitment of high-threshold human motor units during voluntary isotonic lengthening of active muscles. - Nardone, A (1989)
1. We have investigated the possibility that voluntary muscle lengthening contractions can be performed by selective recruitment of fast-twitch motor units, accompanied by derecruitment of slow-twitch motor units. 2. The behaviour of motor units in soleus, gastrocnemius lateralis and gastrocnemius medialis muscles was studied during (a) controlled isotonic plantar flexion against a constant load (shortening contraction, S), maintained plantar flexion, or dorsal flexion resisting the load and gradually yielding to it (lengthening contraction, L), (b) isometric increasing or decreasing plantar torque accomplished by graded contraction or relaxation of the triceps surae muscles, (c) isometric or isotonic ballistic contractions, and (d) periodic, quasi-sinusoidal isotonic contractions at different velocities. The above tasks were performed under visual control of foot position, without activation of antagonist muscles. The motor units discharging during foot rotation were grouped on the basis of the phase(s) during which they were active as S, S + L and L. The units were also characterized according to both the level of isometric ramp plantar torque at which they were first recruited and the amplitude of their action potential. 3. S units were never active during dorsal flexion; some of them were active during the sustained contraction between plantar and dorsal flexion. Most S + L units were active also during the maintenance phase and were slowly derecruited during lengthening; their behaviour during foot rotations was similar to that during isometric contractions or relaxations. L units were never active during either plantar or maintained flexion, but discharged during lengthening contraction in a given range of rotation velocities; the velocity of lengthening consistently influenced the firing frequency of these units. Such dependence on velocity was not observed in S + L units. 4. A correlation was found between the amplitude of the action potential and the threshold torque of recruitment among all the units. In addition, the amplitudes of both the action potential and the threshold torque were higher in the case of L units than in the case of S and S + L units. Most L units could be voluntarily recruited only in the case of ballistic isometric or isotonic contraction. 5. Occasionally, L units were directly activated by electrical stimulation of motor fibres and their conduction velocity was in the higher range for alpha-axons. In contrast, nerve stimulation could induce a reflex activation of S and S + L units.(ABSTRACT TRUNCATED AT 400 WORDS)